A Amazônia de Arthur Reis: entre as "experiências do tempo" e as "intenções do agir" - Sousa, Lademe Correia de (2020)
In the 1960s, it was launched the book A Amazônia e a cobiça internacional, authored by amazon Arthur César Ferreira Reis. In this book, the author denounced the imminent loss of the Amazon, which was under threat of being taken by foreign nations. This speech, that arrogated for itself the authority of the history with views to settle "in true" and, therefore, to have the necessary credibility, insofar as it was under serious denunciation, required a decision by the State, which, according to the author, should colonize / civilize / develop the Amazon in order to prevent its loss to other nations aware of the economic potential represented by the region. Arthur Reis' historiographic work, which deals predominantly with Amazonian issues, culminating in his political discourse of international greed, has earned him a captive place in national public life. Therefore, understanding the paths of this discourse and its links with the political context in which it was forged is the objective of this thesis, which, besides analyzing the political uses of the past that underpinned the historical representation of Arthur Reis, also proposed to investigate the representations built about the author in the Jornal do Comércio do Amazonas and in a set of printed newspapers from the country, predominantly from Rio de Janeiro and São Paulo.